Efeitos da somatotrofina recombinante bovina na puberdade de novilhas nelore - Arana, David Giraldo [UNESP] (2015)
The present experiment evaluated differences in age and weight at puberty between Nellore heifers (260±34 kg; 12±1 months old) treated with saline (n=15) or recombinant bovine somatotropin (rbST; n=16) every 14 days from 12 until 22 months of age or until puberty attainment. Additionally, we assessed the effect of rbST in subcutaneous fat thickness, plasma GH, IGF-I, leptin, glucose, insulin, and pregnancy in the first breeding season. All heifers were maintained on the same pasture and exposed to a teaser bull with a neck-marker device. Heifers body weight and subcutaneous backfat thickness were obtained every two months, ovaries were evaluated by ultrasound and blood samples collected every 14 days to monitor the presence of CL and plasma hormones concentration. There was no effect of treatment (p≥0.05) on age and weight at puberty or pregnancy in the first breeding season. The backfat thickness between the 12th and 13th rib was not affected by treatment (p≥0.05), however the rump backfat thickness was lower in rbST heifers at 18 and 22 months (respectively, p=0.04; p<0.01). Treatments had no effect (p≥0.05) on weight gain, plasma glucose, GH and IGF-I. The diameter of the largest follicle was smaller in animals of the saline group at 12 months of age (p=0.01) and was correlated with plasma IGF-I in the rbST group (r=0.13; p=0.05). In the saline group, leptin concentration was higher at 12.7 (p=0.02), 13.4 (p=0.01), 14.3 (p=0.04) and 16.2 (p=0.03) months, and insulin concentration was increased at 20.1 months of age (p=0.06). In summary, prolonged treatment with rbST did not change the weight or age at puberty, plasma glucose, GH and IGF-I, however it decreased subcutaneous fat and insulin, increased leptin concentration. It was demonstrated that treatment with rbST did not affect pregnancy in the first breeding season.